Efeito da laminação a quente em ligas Cu-Al-Be-Cr superelasticas - Cândido, Gemierson Valois da Mota (2019)
The versatility of shape memory alloy properties occupies an important place in technological development in various industry sectors. They are usually produced by casting processes and then homogenized. However, to obtain semifinished products on an industrial scale, the ingots from the casting process must be hot worked. During the intense process, surface oxidation of the material and microstructural changes may cause modifications in its original thermomechanical properties. In this sense, the present work aims to study the correlation of the superelasticity behavior in Cu-Al-Be-Cr alloys before and after subjecting it to the hot rolling thermomechanical process. The alloys were produced in a resistance furnace without controlled atmosphere and characterized by optical microscopy, X-ray diffraction, differential scanning calorimetry, thermomechanical properties were evaluated by quantification and superelasticity tests. The results showed that the 30% reduction rolled alloys showed an abnormal grain growth. This abnormal growth in relation to non-rolled alloys caused an increase in phase transformation temperatures, a reduction in critical stresses for induction of martensite and residual deformations and a significant increase in alloy superelasticity.